PRAKTIK POLIGAMI DI KALANGAN PARA KIAI (Studi Konstruksi Sosial Poligami para Kiai Pesantren di Jawa Timur) - Roibin Roibin (El-QUDWAH, 2007)
Historically, the practices of polygamy in some countries in the world almost become an inevitable empirical fact, both formally (frankly) and informally (illegally). On the contrary, polygamy has been a familiar charismatic symbol of the kiais, especially kiais in pesantren in East Java. Thereby, polygamy in one side generally gets a less positive response from public, but on the other side, polygamy is exactly assumed as a distinct social status symbol for a kiai. In connection with the fact, this study will see how the understanding and the practice of polygamy done by kiai in pesantren in East Java is. Then from the understanding, we expect to find typology of kiai based on classification of his socio-religiosity. Besides, this study also wants to know the impact of understanding and practice of polygamy of the kiais against the pattern of institution interaction relation between kiais and society, their students, and their wives. According to its data characteristics, this study uses qualitative method with social definition paradigm. The more relevant approach theory is Berger and Luchmann’s theory of social construction. This theory is expected to see how the dialectic process of the kiais with the essence of polygamy itself. According to the proposed research method, there are three research findings. They are 1) there are two kinds of understanding among the elites of kiai in pesantren about polygamy: normative and sociologic understanding. 2) From the understandings, we know the pattern of socio-religiosity classification; they are normative-theological and normative-humanistic classification. 3) The impact of understanding and the practice of polygamy of kiais mentioned above are related with its pattern of socio-religiosity classification. Normative-theological classification will affect statically to the institution they lead. On the contrary, normative-humanistic classification will give a progressive and dynamic impact to the institution they lead. Keyword: Polygamy, Kiai, Social Construction